Corporate Governance and Firm Performance: The Empirical Evidence of Listed Securities Companies in China - Gong, Yan (2019)
In this paper, Chinese listed securities companies are selected as the research objects to analyze the effect of corporate governance on enterprise performance. The sample data includes corporate governance factors (ownership structure, board structure and executive compensation) and corporate performance indicators (ROE) of 705 listed securities companies in China from 2014 to 2018. This paper uses panel data model and multiple linear regression method to make an empirical analysis. The results show that the company's biggest shareholder shareholding ratio, the top ten shareholders’ shareholding ratio and executive compensation have positive effects on the company's performance, while the scale of the board of directors and independent directors have negative effects on the company's performance. However, there are many standards for measuring corporate performance, and the bind between corporate performance and corporate governance under other standards should also be studied.